State-of-the-Art Polymer Science and Technology in Italy (2019,2020) - Blanco, Ignazio; Pantani, Roberto; Sorrentino, Andrea; Pizzi, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Polymer science and technology in Italy represent long-lasting and interdisciplinary fields in which chemistry, physics, and engineering mix together to produce studies which are considered among the best in the world. Several research groups coming from very different fields often collaborate in the design of the material, of the part, and of the processing technology to obtain innovative products with outstanding, new, and smart properties. Examples of the contributions of Italian research in the field are featured in top journals and conferences throughout the world. This Special Issue collects an overview of polymer science and technology in Italy. The research topics include: polymer composites and nanocomposites; biodegradable polymers; polymers with special properties and smart polymers; advanced characterization of polymers; new and innovative polymer processes; modeling of polymer processing; polymeric materials in additive manufacturing; process-properties relationships; polymeric parts for special applications.